Analysis of actors in the management of Lantebung mangrove ecotourism, Bira village, Tamalanrea district, Makassar city. Issue 1 (October 2020) - Kurniawan, M A; Yusran, Y; Sabar, A
Abstract: Lantebung mangrove ecotourism area has now been designated as a conservation and protection area for coastal ecosystems. The management of the Lantebung mangrove ecotourism area is inseparable from various parties, both from the government and the community around the ecotourism area, to support the success of mangrove ecotourism management. This study aims: to determine the role and interests of each actor in the management of the Lantebung mangrove ecotourism area. The data collection method is used in three stages, namely: snowball samplin method, data triagulation and data verification is done by content analysis. The data analysis stage of this research: identification of actors and their roles, analysis of the interests of the actors and mapping of the interests and effects of each actor. The results showed that the actors involved were Jekomala, Lurah Bira, Makassar city tourism office, fishermen group, marine and fisheries service of South Sulawesi, analysis of interests contained in the Green Belt, biodiversity, education and tourism. Mapping the interests and influence of Keyplayers : Jekomala, Makassar city tourism office, context setter: marine and fisheries service, Birah urban village, subject: Lantebung fishermen group.